Effect of Low Dose Oral Contraceptive Pill on Glycemic and Lipidemic status in Women with Normal and Low BMI (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): Aim of the study was to explore the effect of the most widely used low dose OCP (Shukhi) on glycemic and lipidemic factors of under weight (Low BMI) Bangladeshi women.Materials and Methods: This case control study was conducted at the Department of Cell and Molecular Biology, Research Division, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM) and Family Planning Center of Dhaka Medical College Hospital during the period of Jan 2011 to Dec 2011. A total number of 40 women were included in this study having age range between 25-45 years. Twenty nine (29) were with normal BMI (>18.5) and 11 were with low BMI (